Musculoskeletic disorders in workers of tire manufacturing: analysis of the work process and risk of the activity - Zamora Macorra, Mireya; Martínez Alcántara, Susana; Balderas López, Maribel (Acta Universitaria, 2019)
Osteoarticular morbidity of occupational origin is estimated at 30%, both in industrialized and developing countries. Therefore, the objective of this study was to evaluate the association of low back pain, musculoskeletal disorders, and the demands of the work process of tire manufacturing. Also, the risk of back injury in a job by manual handling of loads was evaluated. This is a cross-sectional study. The sample consisted of 185 operators that carry out production activities. The results showed a prevalence of low back pain of 20% and musculoskeletal disorders in upper and lower limbs of 30%, in relation to the risk of manual handling of loads. A high risk was found for the development of dorsolumbar injury. It is concluded that there is a need to reinforce measures that mitigate or minimize musculoskeletal damages derived from the inherent requirements of the technical process.